Manajemen Komunikasi Prodi Dalam Meningkatkan Minat Dan Bakat Bakat Jurnalistik Di Fakultas Dakwah Dan Ilmu Komunikasi Iain Padangsidimpuan - Mhd. Latip kahpi (FDIK IAIN Padangsidimpuan, 2022)
Abstract This research is related to the field of Islamic Broadcasting Communication science which relates to journalistic interests and talents in Islamic Broadcasting Communication students. By using journalistic theories such as journalistic functions, journalistic categories, basic journalistic language, journalistic code of ethics. This type of research uses field research, based on data analysis, this research includes qualitative research with descriptive methods. The data collection method was carried out by non-participant observation, unstructured interviews and documentation. Sources of data were taken and divided into two types, namely primary data which were students of Islamic Broadcasting Communication class 2018, 2019, 2020 and secondary data, which were lecturers of journalism and builder of Student Citizen Journalists (CJM). As for the results of this study, not all of the Islamic Broadcasting Communication students have an interest in journalism, although they have been prepared but have no experience. The Faculty of Da'wah and Communication Studies in general has provided journalism courses as a reference for Islamic broadcasting communication students in order to develop their interests and talents. However, of course it all did not go smoothly as expected, there must be causes or inhibiting factors including: lack of availability of facilities, practice in the field, mental sharpening, mastery of knowledge, and infrastructure at the Faculty of Da'wah and Communication Studies. Keywords: Interest, Student, Talent, Journalism. AbstrakPenelitian ini berkaitan dengan bidang ilmu Komunikasi Penyiaran Islam yang berhubungan dengan manajemen komunikasi kaitannya dengan minat dan bakat jurnalistik pada mahasiswa komunikasi Penyiaran Islam. Dengan menggunakan teori-teori jurnalistik seperti fungsi jurnalistik, kategori jurnalistik, dasar bahasa jurnalistik, kode etik jurnalistik. Jenis penelitian ini menggunakan penelitian lapangan (Field Research), berdasarkan analisis data penelitian ini termasuk penelitian kualitatif dengan metode deskriptif. Metode pengambilan data dilakukan dengan observasi non partisipan, wawancara tidak terstruktur dan dokumentasi. Sumber data diambil dan dibagi dalam dua jenis yaitu data primer yang merupakan mahasiswa Komunikasi Penyiaran Islam angkatan 2018, 2019, 2020 dan data sekunder yang merupakan dosen jurnalistik dan pembina Citizen Jurnalis Mahasiswa (CJM). Adapun hasil penelitian ini, bahwa mahasiswa Komunikasi Penyiaran Islam tidak semuanya memiliki minat dalam bidang jurnalistik, walau sudah dipersiapkan namun tidak ada pengalaman. Fakultas Dakwah dan Ilmu Komunikasi pada umumnya telah memberikan Mata kuliah jurnalistik sebagai acuan untuk mahasiswa komunikasi penyiaran islam agar dapat mengembangkat minat dan bakat nya. Akan tetapi, tentu itu semua tidak berjalan lancar sesuai dengan harapan, pasti ada penyebab atau yang menjadi faktor penghambat diantaranya yaitu: kurangnya ketersediaan fasilitas, praktek ke lapangan, mengasah mental, mengusai ilmu, serta sarana prasarana di Fakultas Dakwah dan Ilmu Komunikasi.Kata kunci: Minat, Mahasiswa, Bakat, Jurnalistik.